2020
DOI: 10.1002/wsb.1081
|View full text |Cite
|
Sign up to set email alerts
|

Golf Courses as Potential Habitat for Urban Coyotes

Abstract: Wildlife increasingly live in and adapt to urban landscapes as natural habitat becomes urbanized. Many carnivores take advantage of undeveloped or open developed areas called green spaces, such as parks or cemeteries, to meet their requirements in urban areas. For instance, coyotes (Canis latrans) expanded their range across most of North America into metropolitan areas and even within highly developed areas, where home ranges of coyotes are associated with green spaces or areas that humans used least. Golf co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Both common and threatened species play significant role in urban ecosystem functioning and provides multitude of ecosystem services. For example, in an experimental study conducted across three towns of UK reported higher amount of carcass removal in the presence of three urban vertebrate scavengers than in their absence (Inger et al, 2016).Varying in size and shape green spaces in urban areas ranges from city parks, remnant forest patches, golf courses to cemeteries act as hotspots of biodiversity (Gallo et al, 2017;Wurth et al, 2020). Variety of green habitats in urban areas covered partially or completely by any type of vegetation under private or public ownership are collectively known as urban green spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Both common and threatened species play significant role in urban ecosystem functioning and provides multitude of ecosystem services. For example, in an experimental study conducted across three towns of UK reported higher amount of carcass removal in the presence of three urban vertebrate scavengers than in their absence (Inger et al, 2016).Varying in size and shape green spaces in urban areas ranges from city parks, remnant forest patches, golf courses to cemeteries act as hotspots of biodiversity (Gallo et al, 2017;Wurth et al, 2020). Variety of green habitats in urban areas covered partially or completely by any type of vegetation under private or public ownership are collectively known as urban green spaces.…”
Section: Introductionmentioning
confidence: 99%
“…First, we found that Shannon-Wiener diversity was higher in study sites where the dominant habitat was an urban natural habitat rather than a human-altered habitat. Although some mammals may thrive in human-altered habitats, like golf courses and cemeteries (Gallo et al, 2017;Wurth et al, 2020), most mammals tend to have higher persistence in urban natural areas, or habitats that consist of large patches of secondary growth forest and shrubs (Atwood et al, 2004;Baker and Harris, 2007). It has also been found that manicured lawns and artificial nocturnal illumination, as seen in parks, golf courses, and cemeteries, may limit dispersal (Mahan and O'Connell, 2005;Fitzgibbon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how animals habituate requires detailed data on individual and group‐level behavior, a challenging undertaking with species that have large home ranges, such as most carnivorans. Indeed, most of the work on urban coyotes has relied on tagging technology for tracking individuals (Breck et al, 2019; Gehrt et al, 2011; Gese et al, 1989; Poessel et al, 2013; Shivik et al, 1997; Thompson et al, 2021; Wurth et al, 2020). While remote telemetry and tagging yields high‐quality and fine‐grained data on animal movement and ecology, it is costly both in terms of budgets and impact to telemetered animals (Burrows et al, 1994; Hopkins & Milton, 2016).…”
Section: Introductionmentioning
confidence: 99%